Ghana : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2012)
Ghana has pursued several programs to accelerate the growth of the economy. In 1995, the government presented 'Ghana: Vision 2020,' aimed at making Ghana a middle-income country in 25 years. Vision 2020 focused on human development, economic growth, rural development, urban development, infrastructure development, and an enabling environment. It was followed by the Ghana Poverty Reduction Strategy. One of the main challenges to economic growth is the unemployment problem. The recent discoveries of oil and gas create tremendous opportunities for stimulating national development.